OP0278 BIOMARKER PROFILING REVEALS NOVEL MECHANISTIC INSIGHTS INTO USTEKINUMAB THERAPEUTIC RESPONSES IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Cesaroni, Matteo; Seridi, Loqmane; Jordan, Jarrat; Sweet, Kristen; Keying, MA; Franks, Carol; Schreiter, Jessica; Lipsky, Peter; Vollenhoven, Ronald van; Hahn, Bevra H.; Rose, Shawn; Baribaud, Frederic; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a heterogenous autoimmune disease that causes progressive organ damage. The cytokines type I interferon (IFN-I), IL-12 and IL-23 have all been shown to contribute to SLE pathogenesis. We previously reported that treatment with ustekinumab (UST), an anti-IL-12/23 p40 neutralizing monoclonal antibody, improved global and organ-specific measures of disease activity in a randomized, placebo (PBO)-controlled study of patients with active SLE (NCT02349061 ). 1 Here, we utilized biomarker data from this clinical study to elucidate the mechanism of action of UST in SLE. Objectives: We aimed to determine whether modulation of IL-12, IL-23, or both cytokines was associated with clinical efficacy, and to ascertain whether UST treatment could modulate IFN-I or improve disease activity in patients exhibiting an elevated IFN-I signature at baseline. Methods: A Phase 2, placebo (PBO)-controlled study enrolled 102 patients with seropositive SLE and active disease despite standard-of-care therapy. 1 Patients were randomized 3:2 to receive UST IV ∼6 mg/kg or PBO at week 0, then subcutaneous injections of 90mg UST q8w or PBO. Whole blood RNA from PAXgene tubes and serum were collected over 24 weeks. Age and sex-matched healthy controls were also studied. Serum IFN-γ, and IL-17A, IL-17F and IL-22 levels were quantified by ELISA as indicative of the IL-12 and IL-23 pathways, respectively, and an IFN-α ELISA was utilized to quantify the IFN-I pathway. Whole blood RNA was assessed for gene expression by microarray. Two Th17 2, 3, an IFN-γ 4 gene signature and 21-gene IFN-I signature (IGS) 5 were analyzed. SLE Responder Index (SRI)-4 at week 24 was used to define UST response (UST-R) and non-response (UST-NR). Results: Serum IL-17A, IL-17F and IL-22 levels and Th17 gene signature levels in blood remained largely stable over the course of 24 weeks in all treatment groups. In contrast, UST-R was associated with a durable reduction in IFN-γ protein and IFN-γ gene signature levels relative to baseline, which was not observed in UST-NR or PBO patients. IGS levels were elevated in 67% of patients at baseline versus healthy controls. Serum IFN-α levels and IGS levels in blood were not modulated by UST treatment through week 24. Baseline IFN-I signature status did not associate with response to UST, as the treatment effect size (UST vs PBO) was similar in IGS low (Δ=27%) and high (Δ=28%) patients. Conclusion: Response to UST was associated with reductions in IFN-γ levels, whereas IL-17A, IL-17F, IL-22 and IFN-I remained largely unchanged. While these findings require confirmation in an ongoing Phase 3 study, these data implicate the involvement of the IL-12 pathway and suggest a novel mechanism of action for UST-R in SLE. References: [1] VanVollenhovenR. Lancet. 2018;392:1330. [2] ZhangW. PLoS One. 2012;7:e38510. [3] ZhangH. JAllergyClinImmunol. 2013;132:1005. [4] WelcherAA. ArthritisRheumatol. 2015;67:2713. [5] YaoY. HumGenomicsProteomics. 2009;doi:10.4061/2009/374312. Disclosure of Interests: Matteo Cesaroni Employee of: Janssen Research & Development, LLC, Loqmane Seridi Employee of: Janssen Research & Development, LLC, Jarrat Jordan Employee of: Janssen Research & Development, LLC, Kristen Sweet Employee of: Janssen Research & Development, LLC, Keying Ma Employee of: Janssen Research & Development, LLC, Carol Franks Employee of: Janssen Research & Development, LLC, Jessica Schreiter Employee of: Janssen Research & Development, LLC, Peter Lipsky Consultant for: Consulting fees from Horizon Pharma, Ronald van Vollenhoven Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, GlaxoSmithKline, Pfizer, Roche, and UCB, Consultant for: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, and Vertex., Speakers bureau: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, and Vertex., Bevra H. Hahn Grant/research support from: Janssen Research & Development, LLC, Shawn Rose Employee of: Janssen Research & Development, LLC, Frederic Baribaud Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, Matthew J Loza Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, Kim Campbell Employee of: Janssen Research & Development, LLC, George Tsokos Grant/research support from: Janssen Research & Development, LLC